PRIORITĂŢILE HIPOCLORITULUI DE SODIU ÎN EFICIENTIZAREA PROCESULUI DE DEZINFECTARE A APEI POTABILE - Lidia Lidia; Eugenia MELENTIEV; Nadejda ŞATOV (Acta et Commentationes: Ştiinţe Exacte şi ale Naturii)
The paper presents the efficiency of drinking water disinfection with sodium hypochlorite. The study of drinking water found that drinking water Chisinau, which is disinfected with sodium hypochlorite, meets all international parameters. It defines its quality. And most importantly, drinking water does not contain an excess of chlorine - a toxic substance, which is one of the most harmful substances to human health.